1998
DOI: 10.1007/s001270050074
|View full text |Cite
|
Sign up to set email alerts
|

Social and clinical factors influencing the choice of coping strategies in relatives of patients with schizophrenia: results of the BIOMED I study

Abstract: The impact of social and clinical factors on the choice of coping strategies of a sample of 236 relatives of patients with schizophrenia, living in five European countries, was explored using well-validated questionnaires. The adoption of problem-focused coping strategies was more frequent among young relatives and among relatives of younger patients, and was associated with higher levels of practical and emotional social support and of professional help. In contrast, emotion-focused strategies were more frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
1
18

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 14 publications
6
61
1
18
Order By: Relevance
“…Questo dato e probabilmente legato alle differenze nelle strategic di coping nei confronti di queste patologie, messe in atto da individui con livello di istruzione diverso (Magliano et al, 1998;Hillert et al, 1999). Infatti, mentre un alto livello di istruzione risulta associato a strategic quali la ricerca di informazione, che a sua volta facilita l'interpretazione di comportamenti e sintomi nell'ambito di una etichetta diagnostica, un basso livello di istruzione si associa all'uso di strategic emotion-oriented quali il rifiuto di interpretare questi disturbi come segno di patologia mentale e Fevitamento dei pazienti con conseguente maggiore distanza sociale (Link et al, 1991).…”
Section: Opinioni Su Competenza Sociale E Diritti Civili Dei Pazientiunclassified
“…Questo dato e probabilmente legato alle differenze nelle strategic di coping nei confronti di queste patologie, messe in atto da individui con livello di istruzione diverso (Magliano et al, 1998;Hillert et al, 1999). Infatti, mentre un alto livello di istruzione risulta associato a strategic quali la ricerca di informazione, che a sua volta facilita l'interpretazione di comportamenti e sintomi nell'ambito di una etichetta diagnostica, un basso livello di istruzione si associa all'uso di strategic emotion-oriented quali il rifiuto di interpretare questi disturbi come segno di patologia mentale e Fevitamento dei pazienti con conseguente maggiore distanza sociale (Link et al, 1991).…”
Section: Opinioni Su Competenza Sociale E Diritti Civili Dei Pazientiunclassified
“…In Bonn, whilst positive communication had the higher score, it was also reported the frequent use of keeping by itself personal interests. On the other hand, search for spiritual help was more frequent in Naples, Athens and Lisbon [4].…”
Section: Introductionmentioning
confidence: 98%
“…Magliano et al 1998 [4], found that problem-centered coping strategies were more frequently used in young relatives and in families of younger patients, which was associated to higher levels of social support and professional help; while the coping strategies centered on emotion were more frequently used in relatives that had lived longer with the patient, which was associated with a poor social support. Rammohan et al 2002 [8], studied religious coping and psychological well-being in caregivers of relatives with schizophrenia in a sample of 60 caregivers; evaluating: intensity of the religious beliefs, perceived burden, religiosity and other coping strategies and psychological wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-cultural studies have shown that the burden on the family and the consequences of caregiving differ considerably in different settings and the variance is only partially explained by the features of the patients, carers and their relationship (Magliano et al 1998a(Magliano et al , b, 2000Van Wijngaarden et al 2003).…”
Section: Introductionmentioning
confidence: 99%